Transportation patterns demonstrate inequalities in community participation for working-age Americans with disabilities. (December 2019) - Henly, Megan; Brucker, Debra L.
Highlights: Disability impacts travel by reducing the number of daily trips taken. Trip reduction results in reduction in community and economic participation. Time since disability onset shows adaptive approaches, also highlights barriers. Abstract: This paper utilizes newly available data from the 2017 National Household Travel Survey to examine travel patterns within the U.S. for persons with disabilities. Our analysis finds that having a disability is associated with lower odds of taking a trip for shopping, for social or recreational reasons, for running errands, or for going to work, even after controlling for other characteristics. Length of disability (less than 6 months, more than 6 months, or lifetime) is associated with the type of mobility aid used to support travel, some aspects of day-to-day travel, and the odds of taking a trip for errands, shopping, social, or recreational reasons. Those with a lifetime disability had lower odds of traveling for errands or shopping (OR = 0.68, p < 0.05) compared to those with a temporary or more recent onset of disability, all else constant. We discuss how these findings help to understand differences in economic and social participation among people with disabilities.